Legal Analysis of The Compensation Mechanism for Land Acquisition for Sutet Tower Construction by PLN n Cilincing District - Ardian, Muhammad Fadhil (RechtIdee, 2025)
This study aims to analyze the compensation mechanism in land acquisition for PLN's construction of the 500 kV SUTET tower in Cilincing District, North Jakarta. The research employs a normative legal approach with a case study method, focusing on the application of legal norms and principles in practical implementation. Findings indicate that, from a regulatory perspective, the compensation mechanism is governed by Law No. 2 of 2012 and its derivative regulations, which outline four key stages: planning, preparation, implementation, and final transfer. However, the compensation process for landowners often presents complex legal and social challenges, including land ownership disputes, disagreements over compensation valuation, and the consignment mechanism, which frequently leads to legal claims from affected communities. The study reveals that, despite the systematic regulatory framework for land acquisition, its implementation remains ineffective in fully ensuring justice, transparency, and legal certainty. Disputes over compensation values and limited public participation are key factors contributing to conflicts between PLN and landowners. Therefore, it is essential to optimize deliberation mechanisms, enhance transparency in compensation assessment, and provide legal assistance to affected communities to ensure their rights are fully protected in national strategic land acquisition projects.